Interaction among biofilter microbiome, fecal metabolome and water quality and regulation of sewage discharge in the recirculating aquaculture system of Apostichopus japonicus. (15th March 2023) - Song, Chenyu; Zhou, Yijing; Li, Xian; Dong, Ruiguang; Song, Xiefa; Huang, Zhitao; Dong, Dengpan
Abstract: With the aggravation of environmental pollution caused by traditional culture of Apostichopus japonicus, the concept of A . japonicus recirculating aquaculture system (RAS) came into being. To plan the sewage discharge time reasonably, we explored the temporal variation of water quality, biofilter microbe and fecal metabolome in RAS and relevant mechanism. The results showed that monitored water quality in RAS were within the safe living range of A. japonicus . Proteobacteria and Desulfobacterota were dominant bacteria in biofilter. The RDA results and correlation heatmap showed that NH4 –N and NO2 –N significantly affected the microbial community composition. The expression pattern of fecal metabolites changed with the passage of time after feeding. And ROC curve analysis and VIP bar chart showed that there were inter group biomarkers with predictive performance, which could help to remind timely sewage discharge. Topological analysis of KEGG pathway enrichment showed that metabolic pathways such as alanine, aspartate and glutamate metabolism changed significantly after feeding ( P < 0.01). Additionally, the correlation analysis results showed that biofilter microbe and fecal metabolites were related to water quality ( P < 0.05). Combined with the above research results, this study concluded that the RAS could discharge sewage 25–30 h after feeding. These findings were of direct significance to the management of RAS environment and the protection of A. japonicus healthy growth. Graphical abstract: Image 1 Highlights: Correlation between biofilter microbe, fecal metabolites and water quality proved. Potential metabolic biomarkers such as traumatic acid, paf, etc. were identified. Sewage was recommended to discharge 25–30 h after baiting.